Design of thiol- and light-sensitive degradable hydrogels using Michael-type addition reactions1. Issue 31 (21st August 2015) - Kharkar, Prathamesh M.; Kiick, Kristi L.; Kloxin, April M.
<x xml:space="preserve">Abstract</x> Hydrogels that respond to multiple stimuli (i.e., light, reducing and aqueous microenvironment) were synthesized using thiol-Michael type reaction and degradation kinetics along with release of nanobeads was characterized.